2009
DOI: 10.3832/ifor0507-002
|View full text |Cite
|
Sign up to set email alerts
|

Assessing water quality by remote sensing in small lakes: the case study of Monticchio lakes in southern Italy

Abstract: © iForest -Biogeosciences and Forestry IntroductionAssessing the quality of surface water in lakes, rivers and reservoirs is a key issue for environmental monitoring and management. In Europe, lakes are classified according to eco-regions (Brivio et al. 2001b), ranging from alpine to boreal, from continental to sub-arctic. Each class is based on morphological, vegetational and climatic conditions, which influence the water quality parameters such as chlorophyll concentration, turbidity, suspended sediments, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…The two images were subsequently clipped to the final study area, and radiometrically corrected using the dark object subtraction model (Chavez 1996), a widely applied methodology considered one of the best approaches for the radiometric correction in change detection analysis (Song et al 2001, Lu et al 2002, Hu et al 2004, Schroeder et al 2006, Mancino et al 2009, Wang & Xu 2010. The reliability of the radiometric correction was confirmed using an inter-calibration algorithm between the NDVI images over a test area of the study site.…”
Section: Image Pre-processingmentioning
confidence: 99%
“…The two images were subsequently clipped to the final study area, and radiometrically corrected using the dark object subtraction model (Chavez 1996), a widely applied methodology considered one of the best approaches for the radiometric correction in change detection analysis (Song et al 2001, Lu et al 2002, Hu et al 2004, Schroeder et al 2006, Mancino et al 2009, Wang & Xu 2010. The reliability of the radiometric correction was confirmed using an inter-calibration algorithm between the NDVI images over a test area of the study site.…”
Section: Image Pre-processingmentioning
confidence: 99%
“…Pearson's correlation was carried out between Landsat bands, and chlorophyll and turbidity concentrations to find the most significant relationships. Previous studies [12,14,[16][17][18][19] found a very significant correlation between chlorophyll concentration and water transparency and the relationships among the visible bands. As regards to chlorophyll, the prominent scattering-absorption features of chl-a include strong absorption between 450-475 nm (blue) and at 670 nm (red), and reflectance reaches to peak at 550 nm (green) and near 700 nm (NIR).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, statistical techniques were also applied to find the most significant relationships between water quality parameters and reflectance values of visible band of TM and OLI data and their combinations [10][11][12][13][14][15]. Pearson's correlation was carried out between Landsat bands, and chlorophyll and turbidity concentrations to find the most significant relationships.…”
Section: Resultsmentioning
confidence: 99%
“…Remote sensing is the proven technology which can be visualized spatially and temporally and related methods can be used in establishing various water quality parameters was widely studied. [3][4][5][6][7][8]. Remote sensing has the ability to comprehend the changes in the past, estimate present impacts and gauge the future for effectual planning.…”
Section: Introductionmentioning
confidence: 99%